Sensibilidade de abelhas brasileiras a agrotóxicos: avaliação de risco ambiental baseada no modelo Apis mellifera Linnaeus, 1758 (Hymenoptera, Apidae) - Lourencetti, Ana Paula Salomé (2022)
Ecotoxicological tests realized to assess the environmental risks of pesticides to bees used by countries around the world are based on the protocols developed by the Organization for Economic and Cooperation, where is recommended the use of isolated active ingredients in surrogate species Apis mellifera Linnaeus, 1758 (Hymenoptera, Apidae). Once the representativeness of these protocols concerning the surrogate and pesticide mixtures is pointed out as gaps regarding the pesticide risk assessment, the development of ecotoxicological studies about stingless bees is a crucial step toward achieving a more protective regulatory process in Brazil. The present work evaluated the toxicity of a neonicotinoid commercial product, isolated and combined with an herbicide and a fungicide in three species of stingless bees considered possible surrogates for the assessment of environmental risk in pollinators in Brazil Tetragonisca angustula Latreille, 1811 (Hymenoptera, Apidae), Scaptotrigona postica Latreille, 1807 (Hymenoptera, Apidae) and Melipona scutellaris Laitrelle, 1811 (Hymenoptera, Apidae).Through adapted oral toxicity tests and comparison of the sensitivity of these bees with the current biological model, we highlight that existing protocols do not protect stingless bee biodiversity due to the greater sensitivity found in representatives and due to toxicological interactions when the insecticide was offered in binary combinations. Therefore, it is a major necessity to incorporate these pollinators into the Brazilian environmental risk assessment process and create regulations regarding the use of mixtures before or after pesticide application.